Readdressing nanocavity diffusion in tungsten - De Backer, Andrée; Souidi, Abdelkader; Hodille, Etienne A.; Autissier, Emmanuel; Genevois, Cécile; Haddad, Farah; Della Noce, Antonin; Domain, Christophe; Becquart, Charlotte S.; Barthe, Marie-France (Frontiers in Nuclear Engineering, 2023)
In nuclear fusion (ITER and the future DEMO), components facing the plasma are exposed to high temperature and irradiation which, on the long term, modifies their thermal and mechanical properties and the tritium retention. Tungsten is a candidate material, subject of many studies of the microstructure evolution under various irradiation and temperature conditions. One milestone is the characterization of the defect properties. In this work, we readdress the diffusion of nanocavities on broad ranges of size and temperature and compare with the dissociation, a competing process during the nanocavity growth. Firstly, at the atomistic scale, using Molecular Dynamics, we explore the variety of elementary events involved in the nanocavity diffusion. Secondly, an experimental study of ion irradiated samples, annealed at different temperatures up to 1773 K, reveals the creation and growth of nanocavities on Transmission Electron Microscopy pictures. Thirdly, we perform a multi-objective optimization of the nanocavity diffusion, input of our Object Kinetic Monte Carlo model to reproduce the experimental results. Finally, we discuss our model with a sensitivity analysis of the main inputs developed for these particular conditions, i.e. the source term which combines two cascade databases and the impurities whose interaction with the defects is characterised with a supplemented database of Density Functional Theory calculations. Three domains of nanocavity size are observed. The first one is the small vacancy clusters for which atomistic calculations are possible and the dissociation is negligible. The second one is the small nanocavities for which we provide new diffusion data and where a competition with the dissociation can take place. The third one is the large nanocavities for which, in any case, the dissociation prevents their existence above 1500 K, in absence of stabilizing interface.